Exploring the Scientific Landscape of Teacher Competence: A Scientometric Analysis - Adriana, Retasya; Sutarni, Nani; Ahman, Eeng (FKIP - Universitas Riau, 2025)
Teacher competence is essential in today’s education, where teachers are expected to not only deliver content but also mentor, assess, and support students' character development. With rapid technological changes, diverse student populations, and evolving learning needs, teachers must continuously adapt their competencies. However, previous research has largely focused on local or conceptual discussions, lacking a comprehensive global perspective. This study aims to map the scientific landscape of teacher competence research from 2005 to mid-2025 using a scientometric method based on the PRISMA 2020 framework. A total of 397 peer-reviewed journal articles indexed in Scopus were analyzed using Biblioshiny. The results show a significant increase in publications after 2020, particularly addressing digital competence, inclusive education, and pedagogical knowledge. Germany and the Netherlands are identified as key contributors, while Indonesia exhibits high productivity with limited international collaboration. This study not only highlights thematic trends and influential contributors but also provides practical insights for shaping future teacher development strategies. By uncovering global research patterns, this work contributes to a more adaptive, inclusive, and digitally responsive understanding of teacher competence in an era of educational transformation.